The 'religion of the child': Korczak's road to radical humanism. Issue 1 (2nd January 2017) - Silverman, Marc
Abstract: This paper explores the biographical and cultural sources that inspired the decision of Janusz Korczak (Warsaw, 1878; Treblinka, 1942) to make his life's vocation the education of young children from dysfunctional families. This decision emerged out of the radical version of humanism he embraced. His identification of children as the population his humanist ethos must serve, distinguishes it from other versions of humanism. The paper explores the role his sense of self and his identification with Poles, Jews, and humanity play in the composition of this humanism. It identifies the hybridity of his cultural identifications as its heart. It proposes that the tensions between these identifications in general, and his non-Jewish Jewish identification that situated him as being 'a part of' and 'apart from' Polish society in particular, induced Korczak to create a universal religion of children in which religious, ethnic, or physical distinctions do not generate prejudice, intolerance, and violence.